Intercultural communication : globalization and social justice - Sorrells, Kathryn (California Sage Publications, 2016)
This student introduction examines intercultural communication within the geopolitical, economic, and cultural context of globalization. It takes a social justice approach and provides a framework to create a more fair and equitable world through communication.
Opening the conversation : studying intercultural communication -- Understanding the context of globalization -- Globalizing body politics : embodied verbal and nonverbal communication -- (Dis)placing culture and cultural space : locations of nonverbal and verbal communication -- Privileging relationships : intercultural communication in interpersonal contexts -- Crossing borders : migration and intercultural adaptation -- Jamming media and popular culture : analyzing messages about diverse cultures -- The culture of capitalism and the business of intercultural communication -- Negotiating intercultural conflict and social justice : strategies for intercultural relations -- Engaging intercultural communication for social justice : challenges and possibilities for global citizenship.
Includes bibliographical references (pages 267-283) and index.
Keywords: Intercultural communication; Globalization -- Social aspects; Social justice; Globalization -- Social aspects; Intercultural communication; Social justice